Investing in Canada's nursing workforce post-pandemic: A call to action - Gail Tomblin Murphy; Tara Sampalli; Lisa Bourque Bearskin; Nancy Cashen; Greta Cummings; Annette Elliott Rose; Josephine Etowa; Doris Grinspun; Esyllt W. Jones; Mélanie Lavoie-Tremblay; Kathleen MacMillan; Cindy MacQuarrie; et al. (Canadian Science Publishing, 2022)
Nurses represent the highest proportion of healthcare workers globally and have played a vital role during the COVID-19 pandemic. The pandemic has shed light on multiple vulnerabilities that have impacted the nursing workforce including critical levels of staffing shortages in Canada. A review sponsored by the Royal Society of Canada investigated the impact of the pandemic on the nursing workforce in Canada to inform planning and implementation of sustainable nursing workforce strategies. The review methods included a trend analysis of peer-reviewed articles, a jurisdictional scan of policies and strategies, analyses of published surveys and interviews of nurses in Canada, and a targeted case study from Nova Scotia and Saskatchewan. Findings from the review have identified longstanding and COVID-specific impacts, gaps, and opportunities to strengthen the nursing workforce. These findings were integrated with expert perspectives from national nursing leaders involved in guiding the review to arrive at recommendations and actions that are presented in this policy brief. The findings and recommendations from this policy brief are meant to inform a national and sustained focus on retention and recruitment efforts in Canada.